Unhealthy foods taste better among children with lower self-control. (1st August 2019) - Ha, Oh-Ryeong; Lim, Seung-Lark; Bruce, Jared M.; Bruce, Amanda S.
Abstract: Self-control is important for healthy eating. Achieving and maintaining healthy eating behaviors can be challenging for children. Susceptibility to palatable unhealthy foods with high sugar, fat, and/or salt is a biologically predisposed, dominant response that can hinder healthy eating decisions. Self-control can help adults to build automatized strategies for resisting susceptibility to unhealthy foods. Likewise, if self-control helps children to learn strategies for resisting susceptibility to unhealthy foods, susceptibility to unhealthy foods would be demonstrated in children with low self-control. Specifically, the association between unhealthiness and tastiness (i.e., unhealthy foods taste better) is one of the important mechanisms underlying susceptibility to unhealthy foods. We expected susceptibility to unhealthy foods to be indicated by the association between unhealthiness and tastiness, as well as better taste perception of unhealthy foods and unhealthy food preferences. In our study, fifty-nine children aged 8–13 years reported their perceived self-control, and completed computerized food rating tasks measuring their healthiness, taste, and preference ratings on 30 healthy and 30 unhealthy foods. Results showed that children with lower self-control demonstrated heightened susceptibility to unhealthy foods, but children with higher self-control did not. Our findings suggested that higher levels of self-control would help children to develop healthy eating strategies for regulating dispositional susceptibility to unhealthy foods.